Pengaruh Pemasaran Media Sosial Instagram Terhadap Booking Intention Dengan Brand Image Sebagai Variabel Intervening di Harris Resort Barelang Batam - M Ikhwanul Fajri; Feri Ferdian (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
This study discusses how the influence of Instagram social media marketing on booking intention through brand image at Harris Resort Barelang Batam. This research is motivated by the discovery of phenomena regarding Instagram social media marketing, booking intention and brand image of Harris Resort Barelang Batam. This type of research is quantitative causal associative, obtained a sample size of 182 respondents and purposive sampling procedures. The Likert scale was used to compile a questionnaire which was used as a research instrument. The data that has been collected is then analyzed through Structural Equation Modeling with Partial Least Square (SEM-PLS) version 3.0. The results of hypothesis testing show that brand image is positively and significantly influenced by social media marketing with a t-statistic value (16.974) > t-table value (1.96) and a p-value of 0.000 <0.05. Booking Intention is positively and significantly influenced by social media marketing, with a t-statistic value (6.915) > t-table value (1.96) and p-Value 0.000 <0.05. Booking Intention is positively and significantly influenced by brand image, with a tstatistic value (7.939) > t-table value (1.96) and p-Value 0.000 <0.05. social media marketing has a significant effect on booking intention through brand image. with a t-statistic value (7.182) > t-table value (1.96) and p-Value 0.000 <0.05.